Analysis of the Level of Efficiency and Effectiveness in Measuring Financial Performance at the Secretariat of the DPRD of West Sumatra Province in 2020-2021 - Dety Lafera (Journal of Accounting and Finance Management, 2022)
This study aims to determine and analyze the level of effectiveness and efficiency in measuring financial performance at the Secretariat of the DPRD of West Sumatra Province for 2020-2021 which is measured using shopping variance analysis, shopping growth analysis, shopping harmony analysis, and shopping efficiency. The research method used is quantitative research. In this study, data collection techniques were carried out by means of documentation and interviews. The data type used is secondary data. The results of this study show that the performance of the capital expenditure budget as seen from the analysis of expenditure variance in 2020-2021 shows that the expenditure variance is in good condition but the realization of spending is far from the planned expenditure budget. The performance of the capital expenditure budget is seen from the growth of growth expenditures fluctuating and in 2020-2021 the growth is negative but is said to be capable because the growth is positive. The performance of the expenditure budget as seen from the analysis of spending harmony in 2020-2021 has not reached the portion in general and has not been able to carry out activities for the needs of its development activities because the portion has not been able to reach the portion in general. The performance of the capital expenditure budget is seen from the expenditure efficiency ratio in 2020-2021, each of which is said to be good because the realization of the budget does not exceed the budget and this shows that the Secretariat of the DPRD of West Sumatra Province has made savings on the budget.